Diaphragmatic hernia in a term newborn with congenital myotonic dystrophy: case report - Pezzoli, Francesco; Parigi, Sara; Moroni, Marco; Sacchini, Michele; Mancano, Giorgia; Zulli, Andrea; Morini, Francesco; Sandini, Elena; Berti, Elettra; Gabbrielli, Gabriella; Serafini, Lisa; Agostini, Elisabetta; et al. (Acta Biomedica Atenei Parmensis, 2023)
Background and aim Myotonic dystrophy (DM) is a genetic disorder determined by an amplified trinucleotide CTG repeat in the untranslated region of the DMPK gene on chromosome 19q13.3. The incidence of the congenital form is 1 in 47619 live births and the mortality in the neonatal period is up to 40%.Methods: We report a case of congenital DM (CDM, also designated Myotonic Dystrophy Type 1), presented with congenital right diaphragmatic hernia and cerebral bilateral ventricular dilatation, genetically diagnosed.Conclusions: Since no case of congenital diaphragmatic hernia associated with CDM is reported, the present case report could be considered of particular interest